American and British Efforts to Democratize Schoolbooks in Occupied Italy and Germany from 1943 to 1949. Issue 1 (1st March 2020) - Weiner, Daniela R. P.
Abstract: During the Allied occupation of the Axis countries, education and the revision of educational materials were seen as a means of ensuring future peace in Europe. Most scholarly literature on this topic has focused on the German case or has engaged in a German-Japanese comparison, neglecting the country in which the textbook revision process was first pioneered: Italy. Drawing primarily on the papers of the Allied occupying military governments, this article explores the parallels between the textbook revision processes in Allied-occupied Italy and Germany. It argues that, for the Allied occupiers involved in reeducation in Italy and Germany, the reeducation processes in these countries were inextricably linked. Furthermore, the institutional learning process that occurred in occupied Italy enabled the more thorough approach later applied in Germany.